PERSEPSI ANGGOTA GEREJA MASEHI ADVENT HARI KETUJUH JEMAAT MANGKUPA KOTA MARUDU, SABAH, MALAYSIA TENTANG IMPLIKASI PERSEMBAHAN KORBAN PAGI DAN PETANG DALAM IBADAH KELUARGA BAGI KEHIDUPAN KRISTEN BERDASARKAN KELUARAN 29:41-42 - Junim, Alfred Joshia; Sagala, Rudolf W. (Fakultas Filsafat Universitas Advent Indonesia, 2020)
In this research, author has identified regarded on implications offerings in familyworship on daily Christian life based on Exodus 29:41 – 42 and based on view ofMangkupa Marudu Town, Sabah, Malaysia Seventh – day Adventist (SDA) churchmembers. This Research has four indicators: meaning on theological base on Exodus29:41 – 42; Explaination on offering morning and evening performed during ancientIsraelites; Application offering morning and evening in relevance on family worshipin Christian family and; Adventist view based on Mangkupa church aboutimplications offerings morning and evening in family worship in daily Christian life.This research divided into two main categories: teories and field research. Resultsfrom this research is that application from offerings morning and evening on ancientIsraelites specially on family worship, as far we know that this ceremony refers todaily sacrifice based on Exodus 29:38 – 46, that mentions there is no specific foratonement for sins and only focus on worship of God, professor from United Statesand later become teacher in University Advent Indonesia for many years, Sir RobertL. Hancock said this fact in his syllabus. Offering morning and evening also, thepriest will become representive for all Israelites to bring the sheep to the altar andoffer it to the Lord. Based on EGW writings, applications that can be observed fromthe morning and evening sacrifice ceremony is in the Christian custom of prayer andspiritual songs every day, morning and evening, that is leaded by leader of the familythat is father who lead the family worship. Every family should doing the dailymorning and evening worship that lead into spiritual growth and developmentChristlike. Results from response shows that they agree by interpretation based onquestioner P11 – P15 .